Development of a facile and sensitive fluorimetric derivatization reagent for detecting formaldehyde. Issue 13 (10th March 2016) - Liu, Chao; Cheng, An-Wei; Xia, Xue-Kui; Liu, Yu-Fa; He, Sheng-Wen; Guo, Xu; Sun, Jin-Yue
Abstract : In this study, a rapid, facile and sensitive derivatization reagent for detecting formaldehyde has been developed. Abstract : Formaldehyde is one of the main environmental pollutants and has significant impacts on human health. Herein, we developed a derivatization reagent for detecting formaldehyde rapidly, facilely and sensitively. Upon the introduction of formaldehyde, the reagent exhibited significant enhancement in fluorescence spectra at room temperature within 9 minutes, and the enhanced green fluorescence could be easily observed by the naked eye. Compared with other relevant analytes such as H2 S, CO, NO and benzene, only formaldehyde could elicit the obvious increase in fluorescence. Furthermore, we prepared fluorescent test papers with the reagent and demonstrated their application for the detection of formaldehyde qualitatively.